(untitled) - Lind, Douglas A. (Boston, 2008)
The new edition of Lind’s Statistical Techniques in Business and Economics is a perennial market best seller due to its comprehensive coverage of statistical concepts and methods delivered in a student-friendly, step-by-step format. The text is non-threatening and presents concepts clearly and succinctly with a conversational writing style. All statistical concepts are illustrated with solved applied examples immediately upon introduction
Keywords: Social sciences,Economics,Commercial statistics,Khoa học xã hội,Thống kê xã hội học; Statistical methods,Statistical methods,Phương pháp thống kê